2016
DOI: 10.1080/09638288.2016.1191551
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and physical function after progressive resistance and balance training among older adults after stroke: an exploratory randomized controlled trial

Abstract: Three-month progressive resistance and balance training was associated with reduced fat mass, which was related to improvements in walking capacity in older adults approximately one year after stroke. Implications for rehabilitation   This three-month PRB group exercise program supported by motivational discussions and daily home-based exercises indicate the following:   • Improved walking capacity was associated with a reduction in fat mass.   • IGF-1 is reduced, possibly indicating improved insulin sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This finding suggests that the muscle loss observed in the sarcopenia group was not solely due to the loss of muscle in the affected hemiplegic side. This result corresponds to recent findings by Vahlberg et al [21]; the study reported that BMI showed low total muscle mass and body fat after stroke. In addition, Chang et al [22] reported that SMM was significantly lower in both paralytic and non-paralytic limbs in most patients with disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…This finding suggests that the muscle loss observed in the sarcopenia group was not solely due to the loss of muscle in the affected hemiplegic side. This result corresponds to recent findings by Vahlberg et al [21]; the study reported that BMI showed low total muscle mass and body fat after stroke. In addition, Chang et al [22] reported that SMM was significantly lower in both paralytic and non-paralytic limbs in most patients with disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…The positive impact of telerehabilitation on motor function has been supported by other literature that also found positive outcomes [31, 32]. A systematic review by Langhorne, Coupar and Pollock [31] investigated the effect of common rehabilitation methods on motor recovery.…”
Section: Discussionmentioning
confidence: 82%
“…They found positive outcomes for interventions such as constraint induced movement therapy, task specific training and training with a moving platform. Similarly, an RCT by Vahlberg et al [32] investigated the effectiveness of progressive resistance and balance training for patients with chronic stroke, which resulted in improvement in motor function. An interesting finding in this systematic review was the lack of impact of telerehabilitation on balance.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic and diastolic blood pressure (SBP, DBP) was measured using a mercury sphygmomanometer at a resting state. Fat mass (FM, kg) and fat-free mass (FFM, kg) were measured by Tanita Bioelectrical Impedance MC-180 Analysis (Tanita Corp, Tokyo, Japan), with which FMI [FM (kg)/height (m 2 )] and FFMI [FFM (kg)/height (m 2 )] were calculated as previously described [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%